Impact of Workers Participation on Performance And Productivity: A Systematic literature review - Sonika (Gyan Management Journal, 2019)
Employees are the lifeline of an organization like the human body needs blood to be alive as an organization needs employees to achieve its goals and to become successful. Workers involved in the organization in the form of decision making, profit sharing, ownership will be helpful in increasing their morale and motivation to work so that the organization achieves its goals successfully. It is a systematic literature review;articles from the web of science and Googlescholar are taken into consideration. Systematic literature review of all journals and their classification is done according to different categories and coding is done on the basis of classification. Gaps are found out at last and conclusions and recommendations for the better study in the future.